2021
DOI: 10.1155/2021/1383878
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of Neurokinin-1 Receptor Inhibition Using Aprepitant in the Apoptotic Cell Death through PI3K/Akt/NF-κB Signal Transduction Pathways in Colon Cancer Cells

Abstract: Background. Colorectal cancer (CRC) is recognized as one of the most common malignancies with a high mortality rate worldwide, supporting the necessity for an effective novel antitumor drug to improve current therapy’s effectiveness. Substance P (SP) is the essential member of the tachykinins (TKs) family, which binds to the specific receptors, known as neurokinin-1 receptor (NK1R), exerting its multiple influences such as tumor cell proliferation, angiogenesis, and metastasis. Aprepitant, as a specific NK1R a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In fibroblast-like synoviocytes, aprepitant can inhibit TNFα-induced phosphorylation and degradation of IκBα, the inhibitor of NF-κBp65, as well as attenuate TNFα-induced nuclear translocation and activity of NF-κBp65 ( Liu X. et al, 2019 ). In colorectal cancer, aprepitant can inhibit the NF-κB via PI3K/AKT axis ( Ghahremanloo et al, 2021 ). These data suggest that the activity of NF-κBp65 may play an important role in the analgesic effect of aprepitant on inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…In fibroblast-like synoviocytes, aprepitant can inhibit TNFα-induced phosphorylation and degradation of IκBα, the inhibitor of NF-κBp65, as well as attenuate TNFα-induced nuclear translocation and activity of NF-κBp65 ( Liu X. et al, 2019 ). In colorectal cancer, aprepitant can inhibit the NF-κB via PI3K/AKT axis ( Ghahremanloo et al, 2021 ). These data suggest that the activity of NF-κBp65 may play an important role in the analgesic effect of aprepitant on inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in accordance with the results of the previous investigations, which reported the cytotoxic property for aprepitant in several cancers ranging from solid tumors [ 35 ] to hematologic malignancies [ 36 ]. Ghahremanloo et al also suggested that a single agent of aprepitant diminishes the viability of colon cancer-derived SW480 cells by reducing the intracellular levels of ROS and abrogating the NF- κ B signaling axis [ 37 ]. In glioblastoma, Korfi et al suggested that a higher concentration of aprepitant (35 μ M) is capable of reducing ROS production while increasing the enzymatic activity of superoxidase dismutase (SOD) and catalase [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Or, in triple-negative breast cancer cells, aprepitant attenuated doxorubicin-induced ROS and, thereby, prevented cardiomyopathy [ 43 ]. In colon cancer, Ghahremanloo et al proposed that through suppressing the PI3K/Akt signaling axis and diminishing intracellular levels of ROS, aprepitant decreased the survival of SW480 cells [ 44 ]. It is hard to conclude, but perhaps, NK1R-induced ROS production in some tissues will contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%